2017
DOI: 10.5897/ajmr2016.8372
|View full text |Cite
|
Sign up to set email alerts
|

Association of N2-fixing cyanobacteria with wheat (Triticum vulgare L.) roots

Abstract: Two locally prevailing hetyerocystous cyanobacterial isolates, collected from alluvial clay soil and identified as Nostoc muscorum and Anabaena variabilis, were tested (either singly or mixed) for their potency to colonize the roots of wheat seedlings. N. muscorum formed close association with root hairs, whereas A. variabilis showed loose binding. The mixture of both cyanobacterial strains formed weak association with the roots of wheat seedlings. The tight colonization of N. muscorum led to accumulation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…CW2 improving the nutritional quality of wheat grains, in terms of protein content and important micronutrients (Fe, Cu, Zn, and Mn). El-Zemrany (2017) found that dry weight of the inoculated plant seedlings root with Nostoc muscorum and Anabaena variabilis augmented by more than 3-fold of the control, wherever the shoots were promoted by more than 36% as compared to the control. Burjus et al (2020) studied that mixed of cyanobacteria with less mineral fertilizers was provided wheat growth and yield similar to that achieved by the rate of urea (46% nitrogen) and diammonium phosphate.…”
Section: Introductionmentioning
confidence: 91%
“…CW2 improving the nutritional quality of wheat grains, in terms of protein content and important micronutrients (Fe, Cu, Zn, and Mn). El-Zemrany (2017) found that dry weight of the inoculated plant seedlings root with Nostoc muscorum and Anabaena variabilis augmented by more than 3-fold of the control, wherever the shoots were promoted by more than 36% as compared to the control. Burjus et al (2020) studied that mixed of cyanobacteria with less mineral fertilizers was provided wheat growth and yield similar to that achieved by the rate of urea (46% nitrogen) and diammonium phosphate.…”
Section: Introductionmentioning
confidence: 91%